2002
DOI: 10.1001/jama.287.14.1815
|View full text |Cite
|
Sign up to set email alerts
|

Fish and Omega-3 Fatty Acid Intake and Risk of Coronary Heart Disease in Women

Abstract: Among women, higher consumption of fish and omega-3 fatty acids is associated with a lower risk of CHD, particularly CHD deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
324
3
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 854 publications
(344 citation statements)
references
References 39 publications
9
324
3
8
Order By: Relevance
“…Some studies on fish consumption and health report that fish consumers on average have a healthier lifestyle than nonconsumers (Hu et al, 2002;Oomen et al, 2000). However, in our study we find that there are a higher percentage of overweight and obese persons in the fish group, and the average BMI is higher than for the other groups.…”
Section: Discussioncontrasting
confidence: 81%
“…Some studies on fish consumption and health report that fish consumers on average have a healthier lifestyle than nonconsumers (Hu et al, 2002;Oomen et al, 2000). However, in our study we find that there are a higher percentage of overweight and obese persons in the fish group, and the average BMI is higher than for the other groups.…”
Section: Discussioncontrasting
confidence: 81%
“…The association between EPA and DHA and the risk of non-fatal myocardial infarction (MI) is, however, unclear. Higher fish intake is significantly associated with reduced risk for non-fatal MI (5) , but the associations between EPA and DHA levels in erythrocytes and reduced risk for non-fatal MI were not significant in the Nurses' Health cohort study (6) . Two cohort studies of men also found non-significant relationships between fish intake and the risk of non-fatal MI (7,8) .…”
mentioning
confidence: 85%
“…There are, however, few available clinical outcome data. Two prospective cohort studies among women with type 2 diabetes showed the risk of CHD to be much lower among those with high intakes of n-3 PUFA [3,4], but no randomised controlled clinical outcome trials have been reported and the evidence from secondary prevention trials in non-diabetic populations is conflicting [2,3] with a recent meta-analysis casting doubt on the strength of the evidence [5].…”
Section: Introductionmentioning
confidence: 99%